Basal Secretion of Lysozyme from Human Airways in Vitro - Patricia Roger; Jean-Pierre Gascard; Vincent Thomas de Montpreville; Charles Brink (Mediators of Inflammation)
The aim of this study was to examine the basal release of lysozyme from isolated human lung tissues. Measurements of lysozyme in the fluids derived from lung preparations were performed using a rate-of-lysis assay subsequent to acidification of the biological samples. Lysozyme released from bronchial preparations into fluids was greater than that observed for parenchymal tissues. The lysozyme quantities detected in bronchial fluids were not modified by removal of the surface epithelium. Furthermore, the quantities of lysozyme in bronchial fluids was correlated with the size of the bronchial preparations. These results suggest that the lysozyme was principally secreted by the human bronchi (submucosal layer) rather than by parenchyma tissues and that a greater release was observed in the proximal airways.